Measurement of Quality of Life VII. Statistical Covariation and Global Quality of Life Data: The Method of Weight-Modified Linear Regression - Soren Ventegodt; Joav Merrick (The Scientific World Journal)
Existing standard statistical procedures do not seem to fulfill the needs of the researcher in global quality-of-life (QOL) research, because the most interesting question seems to be the exact size of statistical covariations. A method is necessary if we are to isolate the most important factors connected to quality of life among the thousands of possible factors in life. We have developed a new procedure we call weight-modified linear regression. Unfortunately as demonstrated in the discussion, the procedure is not totally without problems and weaknesses. In spite of the critique, we believe the procedure to be valid for the purpose of estimating the size of the covariation in population studies including psychometric measures of global quality of life. As we need to be certain that the procedure is valid, we hereby invite the scientific community to give us further critique of the method and suggestions for its improvement.